EFEKTIVITAS PERATURAN WALIKOTA PEKANBARU NOMOR 104 TAHUN 2020 TENTANG PEDOMAN PERILAKU HIDUP BARU MASYARAKAT PRODUKTIF DAN AMAN DALAM PENCEGAHAN CORONA VIRUS DISEASE 2019 (COVID-19) DI KOTA PEKANBARU (STUDI KASUS PASAR BAWAH PEKANBARU) - Olifia Nobel Asyraf; Gusliana HB; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The Mayor of Pekanbaru issued Pekanbaru Mayor Regulation Number 104 of 2020concerning Guidelines for New Life Behavior for Productive and Safe Communities in thePrevention and Control of Corona Virus Disease 2019 (COVID-19) in Pekanbaru City.However, its implementation is still not effective. The formulation of the problem in thisresearch are (1) Is this Perwako effective; (2) What are the obstacles that make this Perwakoineffective; and (3) What efforts can be made to make this Perwako effective. The purpose ofthis research is to find out the effectiveness, obstacles and efforts so that Perwako PekanbaruNumber 104 of 2020 concerning Guidelines for New Life Behavior for Productive and SafeCommunities in the Prevention and Control of COVID-19 in Pekanbaru City (Case Study ofPasar Bawah Pekanbaru) is effective.The type of research used in this research is sociological law research. Thepopulation in this study are (1) the Head of Complaints, Policy, and Licensing Services for theInvestment and One Stop Service Office; (2) Deputy Coordinator of the COVID-19 Task ForceSecretariat; (3) Head of the Operations and Public Order Division of the Civil Service PoliceUnit; (4) Bottom Market Manager; (5) Lower Market Visitors; and (6) Lower Market Traders,with a total sample of 44 people. Research location in Pasar Bawah Pekanbaru. Datacollection techniques using observation, interviews, questionnaires and literature, withquantitative data analysis techniques.From the results of the study it was concluded that (1) Perwako Pekanbaru Number104 of 2020 concerning Guidelines for New Life Behavior for Productive and SafeCommunities in the Prevention and Control of COVID-19 in Pekanbaru City (Case Study ofPasar Bawah Pekanbaru) has not been effective; (2) The obstacles that caused theineffectiveness of Perwako Pekanbaru Number 104 of 2020 concerning Guidelines for NewLife Behavior for Productive and Safe Communities in the Prevention and Control of COVID-19 in Pekanbaru City (Case Study of Pekanbaru Bottom Market), namely, as follows: (a) Lackof participation of business actors in providing facilities that support health protocols; (b) Thelegal culture of the community (managers, traders, and visitors) that violates the Perwako;and (c) Compassion on the part of the legal apparatus in imposing fines; (3) Efforts weremade to overcome the violation of Perwako Pekanbaru Number 104 of 2020 concerningGuidelines for New Life Behavior for Productive and Safe Communities in the Prevention andControl of COVID-19 in Pekanbaru City (Case Study of Pasar Bawah Pekanbaru), namely, asfollows: (1 ) Business actors must provide facilities to support health protocols; (2)JOM Fakultas Hukum Universitas Riau Volume IX No. 2 Juli – Desember 2022 Page 2Socialization of Perwako to the public and educating the public about health protocols. Suchas: washing hands properly, how to wear a good mask, and so on; (3) Taking firm actionagainst business actors who violate health protocols.Keywords: Pasar Bawah, COVID-19, Health Protocol